(untitled) (Research, Society and Development, 2023)
The aim of this study was to examine the professional skills that nurses possess and employ in the dermatology and aesthetics job market. The research was carried out by searching scientific databases such as LILACS, SciELO and Google Scholar. The filters applied ensured that the results only included complete works published in the last five years in Portuguese, English and Spanish. The result of this study is an analysis of the skills required to be a nurse specializing in this area and highlights the importance of their role in addressing legal aspects. In conclusion, nurses with training in dermatology and aesthetics are essential in the management and prevention of dermatological diseases. Furthermore, these professionals are able to create and execute health education programs, including educating patients on how to prevent common skin diseases or cancers. They can also detect early signs of skin problems and intervene in a timely manner to prevent the condition from worsening. Their responsibilities include modifying patients’ behavior, educating them and addressing the mental health problems associated with these conditions.